Teaching and Learning of Piano Timbre Through Teacher–Student Interactions in Lessons - Li, Shen; Timmers, Renee (Frontiers in Psychology, 2021)
The ability to play the piano with a variety of timbres requires a performer to have advanced pianistic skills. Little is known about how these skills are acquired and developed in piano lessons and what the role is of elements such as concepts, technique, sonic outcomes, and bodily movements. To investigate the teaching and learning of piano timbre, the lessons of three pairs of university-level teachers and students (two teachers and three students) were observed, during which they behaved as usual in the first two lessons and were asked to use a dialogic teaching approach in the third lesson. Verbal communications of teachers and students about timbre were coded and analyzed, aiming to gain insight into the teaching/learning process of piano timbre and the roles of embodiment and teacher–student interaction in the context of higher music education. The results suggest that piano timbre is not learned through imitation or as “fixed” and objective knowledge, but as a co-constructed conception between the teachers and the students. The meaning of timbre goals in piano lessons is enacted through “in-the-moment” bodily experience and embodied through performance actions. This study contributes to the understanding of piano timbre as a multifaceted phenomenon and illustrates the teacher's role in developing the student's mind–body integration involved in tone production.